Tourist hostel development in the East Taiwan area - CHUN-CHIEH YANG; SU-FANG WU; MEI-YING LU (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: The study aims to provide up-to-date information on the growth of East Taiwan’s hostel industry, which offers tourists a low-cost alternative in the otherwise pricey tourism sector. The area of Hualien County we use as an example is quite small. Since there had been a void in the literature due to the rapid pace of change, this study set out to fill it.Methodology: The SWOT analysis used in this study was developed from data gathered through observation and archival research.Findings: According to this study, East Taiwan is blessed with a wealth of pristine natural resources that are likely to draw in more tourists looking for leisure activities. Challenges unique to the area included erratic weather, a lack of convenient public transportation, and prohibitively high prices. Opportunities included better public transportation and more eco-friendly, active attractions like whale watching, boating, and staying in a hostel or bed and breakfast. Overdevelopment of sites, an over-saturated market, and a workforce with wildly varying skill sets posed risks to the natural environment.Novelty/ Implications: The results suggest that the development should be in sync with local traditional styles, that transportation and roads should be upgraded, that information should be more readily available via specialized websites, and that people should be better trained. It’s important to take precautions to ensure that pristine natural environments aren’t ruined by construction.